Latent Factor Decoding of Multi-Channel EEG for Emotion Recognition Through Autoencoder-Like Neural Networks - Li, Xiang; Zhao, Zhigang; Song, Dawei; Zhang, Yazhou; Pan, Jingshan; Wu, Lu; Huo, Jidong; Niu, Chunyang; Wang, Di (Frontiers in Neuroscience, 2020)
Robust cross-subject emotion recognition based on multichannel EEG has always been a hard work. In this work, we hypothesize there exists default brain variables across subjects in emotional processes. Hence, the states of the latent variables that related to emotional processing must contribute to building robust recognition models. Specifically, we propose to utilize unsupervised deep generative model (e.g., variational autoencoder), to determine the latent factors from the multichannel EEG. Through sequence modeling method, we examine the emotion recognition performance based on the learnt latent factors. The performance of the proposed methodology is verified on two public datasets (DEAP and SEED), and compared with traditional matrix factorization based (ICA) and autoencoder based approaches. Experimental results demonstrate that autoencoder-like neural networks are suitable for unsupervised EEG modeling and our proposed emotion recognition framework achieves inspiring performance. As far as we know, it is the first work that introduces variational autoencoder into multichannel EEG decoding for emotion recognition. We think the approach proposed in this work is not only feasible in emotion recognition, but also promising in diagnosing depression, Alzheimer's disease, mild cognitive impairment, etc., whose specific latent processes may be altered or aberrant compared with the normal healthy control.